The integration of operator-valued functions with respect to vector-valued measures - Tesko, V. A. (Methods of Functional Analysis and Topology, 2012)
We investigate the H-stochastic integral introduced in [24]. It is known that this integral generalizes the classical Ito stochastic integral and the Ito integral on a Fock space. In the present paper we construct and study an extension of the H-stochastic integral which will generalize the Hitsuda-Skorokhod integral.